2017
DOI: 10.1002/cpp.2143
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in alliance and use of techniques over time: A bidirectional relation between use of “common factors” techniques and the development of the working alliance

Abstract: Therapists tend to modulate their use of common factors techniques across treatment. Additionally, when a strong working alliance is developed early in treatment, therapists tend to use more common factors later on. Moreover, high use of common factors techniques is predictive of later improvement in the alliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 71 publications
(115 reference statements)
0
15
0
2
Order By: Relevance
“…attentive listening, expression of warmth, empathy and support; Frank & Frank, 1991;Rosenzweig, 1936;Wampold, 2001). Previous studies have indicated that the MULTI-60 subscales are internally consistent (Cronbach's α >.70;Shrout, 1995) and demonstrate 'good' to 'excellent' inter-rater reliability (0.60 > ρ i > 0.90; Cicchetti, 1994) (see McCarthy & Barber, 2009, McCarthy, Keefe, & Barber, 2016Solomonov, Kuprian, Zilcha-Mano, Gorman, & Barber, 2016;Solomonov, McCarthy, Keefe, Gorman, Blanchard, & Barber, 2017;Zickgraf, Chambless, McCarthy, Gallop, Sharpless, Milrod, & Barber, 2016). Since published, the psychometric properties of the MULTI-60 have been examined in multiple settings and found reliable across samples of patients, therapists, and observers (McCarthy & Barber, 2009;McCarthy et al, 2016;2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…attentive listening, expression of warmth, empathy and support; Frank & Frank, 1991;Rosenzweig, 1936;Wampold, 2001). Previous studies have indicated that the MULTI-60 subscales are internally consistent (Cronbach's α >.70;Shrout, 1995) and demonstrate 'good' to 'excellent' inter-rater reliability (0.60 > ρ i > 0.90; Cicchetti, 1994) (see McCarthy & Barber, 2009, McCarthy, Keefe, & Barber, 2016Solomonov, Kuprian, Zilcha-Mano, Gorman, & Barber, 2016;Solomonov, McCarthy, Keefe, Gorman, Blanchard, & Barber, 2017;Zickgraf, Chambless, McCarthy, Gallop, Sharpless, Milrod, & Barber, 2016). Since published, the psychometric properties of the MULTI-60 have been examined in multiple settings and found reliable across samples of patients, therapists, and observers (McCarthy & Barber, 2009;McCarthy et al, 2016;2017).…”
Section: Introductionmentioning
confidence: 99%
“…Since published, the psychometric properties of the MULTI-60 have been examined in multiple settings and found reliable across samples of patients, therapists, and observers (McCarthy & Barber, 2009;McCarthy et al, 2016;2017). The use of the MULTI-60 has produced findings with important training and clinical practice implications (Boswell, Castonguay & Wasserman, 2010;Castonguay et al, 2017;McCarthy & Barber, 2009;McCarthy et al, 2016;Solomonov et al, 2017;Zickgraf et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that as therapy progresses, ruptures are attributed more significantly by the client and that the therapist's ability to resolve issues has a more significant effect on outcome. Another possible explanation might be differences in flexibility with respect to the technique used by the therapist; for example, Solomonov et al () found a positive bidirectional relation between the use of common factor techniques and the working alliance. More effective therapists might be more flexible, using common factor techniques in differing phases of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Spezielle Arbeiten für den Bereich Kinder-und Jugendlichentherapie deuten auf einen kleinen Zusammenhang zwischen Adhärenz und Outcome hin, wobei in diesem Bereich bisher fast ausschließlich familientherapeutische und verhaltenstherapeutische Ansätze untersucht wurden [7]. Einzelstudien zu Prozessvariablen zeigten bisher, dass die therapeutische Beziehungsqualität nicht mit der domänenspezifischen Kompetenz der TherapeutInnen zusammenhängt [8]. Diese Ergebnisse bedeuten nicht, dass therapeutische Techniken per se keine Wirkung zeigen.…”
Section: Domänenspezifische Kompetenzenunclassified